Human health risk assessment of drinking water using heavy metal pollution index: a GIS-based investigation in mega city - Maria Latif; Iqra Nasim; Mubeen Ahmad; Rab Nawaz; Arifa Tahir; Muhammad Atif Irshad; Aamal A. Al-Mutairi; Ali Irfan; Sami A. Al-Hussain; Magdi E. A. Zaki (Applied Water Science)
Abstract Contaminated drinking water poses a significant threat to public health, particularly in urban areas where industrial and environmental pollutants may affect water quality. However, there is a lack of comprehensive studies that evaluate the specific health risks associated with harmful metal contaminants in drinking water. This study seeks to address this gap by assessing water quality and metal contamination using pollution indices and human health risk assessments. The findings will help to identify potential health risks for urban residents and guide the development of targeted interventions and improved water management strategies. The groundwater samples were collected from five different zones in Kasur rural area. A total of 25 samples were collected by random sampling from hand pumps during 4 months (March–June, 2021) for determining various physiochemical attributes (pH, electric conductivity, turbidity, total hardness, chloride, and phosphate) and potentially toxic elements (arsenic, cadmium, and lead) using standard protocols. Results revealed that almost all the physicochemical attributes were close to the World Health Organization (WHO) guidelines. The water quality assessment revealed that pH levels ranged from 7.4 to 9.0, electrical conductivity (EC) between 150 µS/cm and 800 µS/cm, and average turbidity of 12 ± 3.29 NTU, total hardness varied from 200 to 1000 mg/L. Chloride and phosphate concentrations averaged 304 ± 1.28 mg/L and 4.51 ± 1.99 mg/L, respectively. Cadmium levels ranged from 0.15 to 0.53 mg/L, while lead and arsenic concentrations reached up to 7.47 mg/L, exceeding the WHO guidelines. Heavy metal pollution index (HPI) values of all sites were less than critical value of 100. However, by considering the HPI classes, all the locations had high HPI (> 30) class indicating critically polluted water with heavy metals. Through exposure to drinking water, heavy metals had a significant impact on non-carcinogenic risk (HI > 1), according to the hazard index values determined by the human health risk analysis for children, infants, and adults. As compared with metals carcinogenic risk values, lead posed high risks to adults than children and infants as mean CR values for adults, children, and infants were 1.48E + 00, 1.40E + 00, and 7.60E-01, respectively. It is suggested that for drinking water supplies, there is need of installation of treatment plants in the industrial areas to minimize the risk of metal contamination and health issues.